Department of Microbiology, Science and Research Branch, Islamic Azad University, Tehran, Iran - MOOMIVAND, H; POURBAKHSH, SA; JAMSHIDIAN, M (Journal of the Hellenic Veterinary Medical Society, 2018)
In ostriches, mycoplasmas are generally associated with respiratory diseases and causes rhino-tracheitis, airsacculitis and inflammation of the upper respiratory tract. The aim of current study was the isolation and identification of pathogenic mycoplasmas in ostrich farms of Iran by the use of PCR and culture methods. In this study, mycoplasmas were isolated from ostrich slaughterhouse; 114 samples were collected from ostriches with respiratory signs and were cultured and PCR methods along with alignment were used to detect the mycoplasmas. For this purpose lung, trachea and air sacs were evaluated. The results indicated that 21.05% of samples were positive in PCR assayand from them 7.89% and 14% was M. gallisepticum and M. synoviae, respectively. The highest rate of M. gallisepticum and M. synoviae was detected in lung, airsacs and trachea. Alignment analysis demonstrated that the M. gallisepticum strains detected in our study have 97% homology to 06/14, 05/14 and 16S strains. In addition, M. synoviae strains have 99% and 98% homology to MSR-812, MSR-795 and MSR-1019 strains. One of the M. synoviae strains has 82% homology to ABSfsdMS2011 strain. The results of our study showed that ostriches in Iran were infected with chicken mycoplasmas but the pathogenesis of them in ostrich respiratory should be further evaluated.